Experimental Study of Smart Steel Cables with Tubular Spot-Welded Grating Sensors - Nianchun Deng; Zhongqing Han; Zhiqian Chen; Zhaotao Chen (Sensors)
In this study, a tubular spot-welded grating sensor composed of a stainless-steel tube fixed to a substrate surface by welding is developed, and the tube is filled with high-performance epoxy resin components after the grating sensor is passed through it. A smart steel strand cable is created by spot welding steel strands using portable spot-welding equipment. This method generates a small current during spot welding, with a voltage of only 3 V to 5 V, and does not damage the internal structure of the steel strand. An equation related to the temperature, tension force, and wavelength fluctuation is presented in this article. A method with a transverse temperature coordinate and a longitudinal wavelength coordinate is used. A formula for the standard temperature calibration of the force values and a procedure for temperature adjustment of the force values are presented. The correlation coefficient between the stress on the steel strand and the wavelength of the tubular spot-welded grating sensor is as high as 0.999 according to static tensile testing, demonstrating good repeatability. The temperature adjustment coefficient for varying temperatures is 0.0264 nm/°C, and the test error is essentially limited to 3.0% F.S. When subjected to a 120 h relaxation test, the steel strand with the tubular spot-welded grating sensor exhibits a relaxation rate of 4.44%. The force value obtained after the relaxation test is 1.2% off from the standard load. A tubular spot-welded grating sensor is welded onto a steel strand within a cable sealing cylinder to create an extruded anchor epoxy-coated steel strand cable. The measured cable force is compared with the standard load. The maximum error is 0.5% F.S. The discrepancy between the measured cable force and the acceleration sensor value is 1.5% in one instance involving an arch bridge employing six smart suspension cables to detect cable forces onsite. The findings provide theoretical and engineering references for smart cables and demonstrate the high accuracy, dependability, and fixation performance of the tubular spot-welded grating sensor smart cable.